Caesarean section in the second stage of labour. (18th April 2012) - Graham, N; Gillham, J
Abstract : Objective: Current literature reports concerning trends of rising rates of caesarean section (CS) at full cervical dilatation. All Second stage CS performed over 18 month period reviewed. Method: Retrospective case note review of all patients undergoing second stage CS between October 2009 and April 2011, in a tertiary referral centre with approximately 6000 deliveries per year. Results: During the study period 99 women underwent second stage CS. Of these 44.9% proceeded straight to CS and 55.1% following failed trial of instrumental delivery. Consultant was present in 42.7% of the cases; the senior registrar 55.1%, junior registrar 2.2%, and no cases where the SHO was the most senior person present. A high proportion of cases occurred in nulliparous women (70.8%). 12.4% of cases were attempting VBAC. The main reason for second stage CS was failed rotational delivery (33.7%). An increasing trend for kiwi to be used as the only instrument for trial in theatre was seen. Following review 28.1% of these cases could potentially have had a different outcome had the management been altered/more senior support available. Conclusion: To help reduce numbers of second stage CS reviews of such cases are an important tool in improving understanding and management, areas of concern are highlighted which allows additional training, education and procedures to be implemented. A common theme arising was a lack of confidence amongst juniors in dealing with difficult deliveries and limited experience in using certain equipment. To avoid the potential risks associated with full dilatation CS input from a senior more skilled obstetrician is beneficial.